Disruption of DNA Damage-Response by Propyl Gallate and 9-Aminoacridine. (28th February 2016) - Matsuda, Shun; Matsuda, Yoko; Yanagisawa, Shin-Ya; Ikura, Masae; Ikura, Tsuyoshi; Matsuda, Tomonari
Abstract: The DNA-damage response (DDR) protects the genome from various types of endogenous and exogenous DNA damage, and can itself be a target of certain chemicals that give rise to chromosomal aberrations. Here, we developed a screening method to detect inhibition of Mediator of DNA damage Checkpoint 1 (MDC1) foci formation (the Enhanced Green Fluorescent Protein (EGFP)-MDC1 foci formation-inhibition assay) using EGFP-MDC1-expressing human cells. The assay identified propyl gallate (PG) and 9-aminoacridine (9-AA) as inhibitors of camptothecin (CPT)-induced MDC1 foci formation. We demonstrated that the inhibition of CPT-induced MDC1 foci formation by PG was caused by the direct suppression of histone H2AX phosphorylation at Ser139 (γH2AX), which is required for MDC1 foci formation, by quantifying γH2AX in cells and in vitro . 9-AA also directly suppressed H2AX Ser139-phosphorylation in vitro but the concentration was much higher than that required to suppress CPT-induced MDC1 foci formation in cells. Consistent with these findings, PG and 9-AA both suppressed CPT-induced G2 /M cell-cycle arrest and increased the number of abnormal nuclei. Our results suggest that early DDR-inhibitory effects of PG and 9-AA contribute to their chromosome-damaging potential, and that the EGFP-MDC1 foci formation-inhibition assay is useful for detection of and screening for H2AX Ser139-phosphorylation-inhibitory effects of chemicals.